New Challenging Systemic Therapies for Juvenile Scleroderma: A Comprehensive Review - Chiara Sassetti; Claudia Borrelli; Martha Mazuy; Cristina Guerriero; Donato Rigante; Susanna Esposito (Pharmaceuticals)
Background: Juvenile scleroderma (JS) comprises a group of rare chronic autoimmune and fibrosing disorders in children, primarily presenting as juvenile localized scleroderma (jLS) or juvenile systemic sclerosis (jSS). While jLS predominantly affects the skin and subcutaneous tissues, jSS may involve multiple internal organs and is associated with increased morbidity and mortality. Due to the scarcity of pediatric-specific clinical trials, the current treatment strategies are largely empirical and often adapted from adult protocols. Objective: This narrative review aims to provide a comprehensive update on emerging systemic therapies for juvenile scleroderma, focusing on biologics, small molecule inhibitors, and advanced cellular interventions, to support the development of more personalized and effective pediatric treatment approaches. Methods: A literature search was conducted through PubMed and a manual bibliographic review, covering publications from 2001 to 2024. Only English-language studies involving pediatric populations were included, comprising randomized controlled trials, reviews, and case reports. Additional searches were performed for drugs that are specifically used in juvenile scleroderma. Results: Biologic agents such as tocilizumab, rituximab, and abatacept, along with small molecules including Janus kinase (JAK) inhibitors and imatinib, have demonstrated potential in managing refractory cases by reducing skin fibrosis and pulmonary involvement. Novel approaches—such as pamrevlumab, nintedanib, and chimeric antigen receptor (CAR-T) cell therapy—target fibrotic and autoimmune pathways but remain investigational in children. Autologous stem cell transplantation (ASCT) has also been explored in severe, treatment-resistant cases, although data are extremely limited. The overall evidence base is constrained by small sample sizes, a lack of controlled pediatric trials, and reliance on adult extrapolation. Conclusions: While innovative systemic therapies show promise for juvenile scleroderma, their widespread clinical application remains limited by insufficient pediatric-specific evidence. Large, multicenter, long-term trials are urgently needed to establish safety, efficacy, and optimal treatment algorithms that are tailored to the pediatric population.